PENGELOLAAN PERPUSTAKAAN - Lubis, Sukri Fadli; Hasnawati, Hasnawati (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2024)
3 Kota Pariaman. This can be seen in the process of arranging books which is not good, resulting in some books being placed on the wrong shelves according to their type and some books not being arranged at all. This is due to the lack of bookshelves available in the MTsN 3 Kota Pariaman library. Apart from that, library collections and facilities are considered less comfortable, and lending services are still manual. The aim of this research is to determine the elements of library management. Qualitative data collection methods such as observation, interviews and documentation were used in the research. Information checking strategies used in this exploration include reducing information, displaying information, and determining/checking achievements Research shows that school library management is divided into five main parts, namely collection management, inventory, collection maintenance, library equipment, and administration. Firstly, collection management is done by buying your own books and accepting gifts or donations from students and bookstores. The second activity carried out in the inventory is the study of library materials, then the collection of the variety is completed by collecting them into areas of study. After that, stamps on the front and back pages of the book provide an immediate overview of the library materials. When recording library materials, a stock book is provided. Third, in maintaining library collections, clean books from dust, repair existing damage, and organize book shelves. Fourth, library equipment is still lacking, such as the absence of reading tables and computer tables, bookshelves, and fifth, library administration includes borrowing, returning books and recording visitors.